2019
DOI: 10.31545/intagr/110807
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil quality after biochar application based on enzymatic activity and microbial composition

Abstract: Soil microorganisms play a key role in many biochemical processes essential for the environment and for the ecological and production functions of soils, hence they are very important quality indicators. The study aimed at evaluating the effect of 1 and 2% additions of wheat and miscanthus straw biochars on soil enzymatic activity (dehydrogenases, urease, phosphatases) and the number of microorganisms (bacteria, fungi, actinobacteria). Pot experiments were carried out on soil with a loamy sand texture. The geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…The sorption capacity of charcoal and biochar is determined, among others, by the concentration of heavy metals in the soil solution. In unpolluted soils, the natural consequence of using these materials is the reduction in the content of the most available element forms (Miura and Shiratani, 2018;Mierzwa-Hersztek et al, 2019). In our study, the increase in soil pH after the use of CHAR-C was one of the important factors reducing the content of the most available heavy metals (Gondek and Mierzwa-Hersztek, 2016).…”
Section: Effect Of the Addition Of Cavitated Charcoal On The Content mentioning
confidence: 52%
See 3 more Smart Citations
“…The sorption capacity of charcoal and biochar is determined, among others, by the concentration of heavy metals in the soil solution. In unpolluted soils, the natural consequence of using these materials is the reduction in the content of the most available element forms (Miura and Shiratani, 2018;Mierzwa-Hersztek et al, 2019). In our study, the increase in soil pH after the use of CHAR-C was one of the important factors reducing the content of the most available heavy metals (Gondek and Mierzwa-Hersztek, 2016).…”
Section: Effect Of the Addition Of Cavitated Charcoal On The Content mentioning
confidence: 52%
“…Recent studies indicate that thermally transformed organic materials, including charcoal and biochar, exhibit sorption capacity for heavy metal ions (Miura and Shiratani, 2018;Mierzwa-Hersztek et al, 2019). These materials have a large specific surface area, i.e., a surface on which there are functional groups that are active in the sorbing of heavy metal ions.…”
Section: Effect Of the Addition Of Cavitated Charcoal On The Content mentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators reported that SS added to agricultural soil increased the organic matter content from 1.4 to 4.8% when applied at 20 g kg−1 while, the estimated trace metals in soils were either below Cu, Fe, Mn, Mo, Zn, and Pb or within Co, Ni, Cd, and Cr maximum permissible levels [44]. In addition, Mierzwa-Hersztek et al [45] reported a positive correlation between microbial population and soil pH. Mixing SS amended soil with lime (calcium carbonate) or biochar (a carbon-rich product obtained when biomass, such as wood, manure, or leaves, is heated in a closed container) has been proposed to reduce soil contamination by trace metals due to their impact soil pH [46,47].…”
Section: Resultsmentioning
confidence: 99%